1. The problem statement, all variables and given/known data I got the laplace transfer function H(s) = 1/(s + 2) and I'm suppose to find the inverse Z transform by first converting to H(z) by s = Ts/2*(z-1)/(z+1) Then do inverse Z-transform using the "displacement rule" - Never heard of. 2. Relevant equations H(s) = 1/(s + 2) s = Ts/2*(z-1)/(z+1) 3. The attempt at a solution I can't get any serious answer, and the partial z-inverse that I manage to find it's incredibly complicated (see image). What is this 'displacement rule' and how do I use it here?